1988
DOI: 10.1159/000248567
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Double-Blind Multicenter Study Comparing Acitretin-PUVA, Etretinate-PUVA and Placebo-PUVA in the Treatment of Severe Psoriasis

Abstract: A randomized double-blind study was designed with 65 patients in order to clarify two points: (1) does addition of a retinoid to psoralen-ultra violet A photochemotherapy (PUVA) of severe psoriasis decrease the UVA energy required to achieve remission, and (2) is there a difference between two retinoids, i.e. etretinate and acitretin. Acitretin-PUVA treatment was significantly superior to placebo-PUVA with respect to several items (decrease in lesional scores after 6 weeks of therapy, number of PUVA exposures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(65 citation statements)
references
References 14 publications
2
60
1
2
Order By: Relevance
“…19 The addition of low-dose retinoids enhances both the efficacy and safety of PUVA in patients with severe, widespread psoriasis, as shown by Saurat and colleagues. 26 In a controlled study conducted by 27 observed marked or complete clearing in 96% of the patients receiving rePUVA but only 80% of the patients receiving PUVA and placebo. In both of these studies, the addition of retinoids reduced the dose of UVA needed for clearance by more than 40%.…”
Section: Acitretin and Phototherapymentioning
confidence: 97%
“…19 The addition of low-dose retinoids enhances both the efficacy and safety of PUVA in patients with severe, widespread psoriasis, as shown by Saurat and colleagues. 26 In a controlled study conducted by 27 observed marked or complete clearing in 96% of the patients receiving rePUVA but only 80% of the patients receiving PUVA and placebo. In both of these studies, the addition of retinoids reduced the dose of UVA needed for clearance by more than 40%.…”
Section: Acitretin and Phototherapymentioning
confidence: 97%
“…[26][27][28] These show the acitretin-PUVA combination to be more effective than PUVA alone, reducing the number of PUVA treatments, exposure to ultraviolet (UV) A and the clinical scores, and to be as effective as etretinate-PUVA combination. A trend was seen towards a higher incidence of side-effects in the acitretin-treated patients.…”
Section: Combination Therapy In Psoriasismentioning
confidence: 99%
“…PUVA is often combined with acitretin, an oral retinoid, to increase efficacy and decrease the amount of UVA energy required. 31 Combination therapy has been shown to be superior to PUVA alone, with clearance rates of 80% for PUVA compared with 96% with combination therapy, and was associated with a 42% reduction in the mean cumulative dose of UVA. 28 This combination is thought to potentially decrease toxicity and costs associated with use of either agent alone.…”
Section: Systemic Therapies For Psoriasismentioning
confidence: 99%